Synthesis of ternary-based visible light nano-photocatalyst for decontamination of organic dyes-loaded wastewater. (February 2022) - Nawaz, Arif; Khan, Adnan; Ali, Nisar; Mao, Ping; Gao, Xiaoyan; Ali, Nauman; Bilal, Muhammad; Khan, Hammad
Abstract: The release of dyes-loaded wastewater from various industries is a major threat to human beings due to their health hazard effects. Ternary ferrites-based visible light photocatalyst Fe2 Zn0.5 Cu0.5 O4 -CM (CZF-CM) was formed via the co-precipitation method. These prepared ternary ferrites nanoparticles Fe2 Zn0.5 Cu0.5 O4 (CZF-NPs) and photocatalyst (CZF-CM) were analyzed using different spectroscopic techniques. The average crystallite size of CZF-NPs was calculated from XRD data using Scherer's equation and found to be 12 nm. The elemental composition of the synthesized ternary ferrites nanoparticles (CZF-NPs) was defined by the EDX images. The morphology of CZF-CM photocatalyst is spherical, having a smooth surface and average microspheres size of 810 μm based on SEM micrographs. The photocatalyst has bandgap of 2.57 eV, which lies in the visible range of the electromagnetic spectrum derived by extrapolating Tauc's plot. Photocatalyst CZF-CM showed 94% degradation efficiency for Rhodamine B (RB) dye at optimized conditions of initial dye concentration, catalyst dosage, pH and sunlight irradiation contact time as 40 ppm, 0.7 g, pH 8 and 125 min, respectively. Maximum degradation (96%) of methyl orange (MO) dye occurred at pH 6, at similar optimized conditions as the RB dye. The binary ferrites photocatalyst Fe2 CuO4 -CM (CF-CM) and Fe2 ZnO4 -CM (ZF-CM) of the selected metals showed lesser photocatalytic efficiency than ternary ferrites. An artificial neural network in addition to the response surface methodology was used for the optimization process. The artificial neural network is highly in agreement with the experimental results obtained for the selected dyes. The corresponding predicted response for each data set from ANOVA showed high R 2, R 2 adj, and R 2 pred values for the proposed model. It also indicates that contributing parameters in the model are significant due to having very high F-values and low p-values. It is concluded that the synthesized photocatalysts are considered an efficient entrant for the decolorization of industrial wastewater. Graphical abstract: Image 1 Highlights: Development of ternary-based visible light nanophotocatalyst Fe2 Zn0.5 Cu0.5 O4 -CM. Structural and morphological characteristics were scrutinized using advanced techniques. Highly efficient photocatalytic degradation of organic dyes under sunlight irradiation. Response surface methodology and artificial neural network for optimizing operating factors.